The Conducting Guidebook for Undergraduate Students - Zuopei , Cheng; Roongruang, Panya (Journal of Roi Kaensarn Academi, 2024)
Music conducting, like other music performing arts, requires not only conducting techniques and performance skills, but also a professional textbook as a reference and theoretical guidance. Especially as an undergraduate student, it is very necessary to have a proper conducting guidebook in the process of learning conducting. However, the author found through investigation that undergraduates majoring in conducting do not have a specific guidebook, but only a textbook in general. So the author decided to create a conducting guidebook for undergraduates.The objective of this research are (1) To study conducting with key informants. (2) To construct the conducting guidebook for undergraduate student at Shanghai conservatory of music. (3) To conduct teaching experiment by using guidebook. (4) To evaluate the results of teaching experiment by using guidebook.This research use a mixed research method by using an experimental group with a simply random sampling.